Question

# Write the product in standard form. (2𝑥 + 5)^{2}

Hint:

### The methods used to find the product of binomials are called special products.

Multiplying a number by itself is often called squaring.

For example (*x* + 3)(*x* + 3) = (*x* + 3)2

## The correct answer is: 25

### (2𝑥 + 5)^{2} can be written as (2𝑥 + 5)(2𝑥 + 5)

(2𝑥 + 5)(2𝑥 + 5) = 2x(2x + 5) + 5(2x + 5)

= 2x(2x) + 2x(5) + 5(2x) + 5(5)

= 4x^{2} + 10x + 10x + 25

= 4x^{2} + 20x + 25

Final Answer:

Hence, the simplified value of (2𝑥 + 5)^{2} is 4x^{2} + 20x + 25.

^{2}+ 10x + 10x + 25

^{2}+ 20x + 25

Final Answer:

Hence, the simplified value of (2𝑥 + 5)

^{2}is 4x

^{2}+ 20x + 25.

This question can be easily solved by using the formula

(a + b)2 = a2 + 2ab + b2

### Related Questions to study

### Write the product in standard form. (𝑥 − 7)^{2}

This question can be easily solved by using the formula

(a - b)2 = a2 - 2ab + b2

### Write the product in standard form. (𝑥 − 7)^{2}

This question can be easily solved by using the formula

(a - b)2 = a2 - 2ab + b2

### (𝑥 + 9)(𝑥 + 9) =

This question can be easily solved by using the formula

(a + b)2 = a2 + 2ab + b2

### (𝑥 + 9)(𝑥 + 9) =

This question can be easily solved by using the formula

(a + b)2 = a2 + 2ab + b2

### Find the area of the rectangle.

### Find the area of the rectangle.

### The table below shows the distance a train traveled over time. How can you determine the equation that represents this relationships.

### The table below shows the distance a train traveled over time. How can you determine the equation that represents this relationships.

### Simplify: 4x^{2}(7x -5) -6x^{2}(2 -4x)+ 18x^{3}

### Simplify: 4x^{2}(7x -5) -6x^{2}(2 -4x)+ 18x^{3}

### (𝑎 + (−3))^{2} =

This question can be easily solved by using the formula

(a - b)2 = a2 - 2ab + b2

### (𝑎 + (−3))^{2} =

This question can be easily solved by using the formula

(a - b)2 = a2 - 2ab + b2

### Use the table method to multiply a binomial with a trinomial.

(−3𝑥^{2} + 1) (2𝑥^{2} + 3𝑥 − 4)

### Use the table method to multiply a binomial with a trinomial.

(−3𝑥^{2} + 1) (2𝑥^{2} + 3𝑥 − 4)

### (𝑥 − 2)^{2} =

This question can be easily solved by using the formula

(a - b)2 = a2 - 2ab + b2

### (𝑥 − 2)^{2} =

This question can be easily solved by using the formula

(a - b)2 = a2 - 2ab + b2